Depression and Anxiety Changes Among Sexual and Gender Minority People Coinciding with Onset of COVID-19 Pandemic - Annesa Flentje; Juno Obedin‐Maliver; Micah E. Lubensky; Zubin Dastur; Torsten B. Neilands; Mitchell R. Lunn (2020)
Author(s): Flentje, Annesa; Obedin-Maliver, Juno; Lubensky, Micah E; Dastur, Zubin; Neilands, Torsten; Lunn, Mitchell R